2006
DOI: 10.1158/1055-9965.epi-06-0671
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and Body Size throughout Life in Relation to Sex Hormones and Prolactin Concentrations in Premenopausal Women

Abstract: The association of birthweight and body size throughout life with premenopausal breast cancer risk may be due, in part, to relationships with sex hormones. Therefore, we assessed whether birthweight, body shape at ages 5 and 10, body mass index (BMI) at age 18 and adulthood, adult waist circumference and waist-to-hip ratio (WHR), and attained height were associated with the plasma concentrations of estrogens, androgens, progesterone, prolactin, and sex hormone -binding globulin (SHBG) in 592 premenopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 65 publications
11
93
1
Order By: Relevance
“…An inverse relation of birth size with adrenal androgen levels in 8-year-old children has also been found for children of normal birth size (Ong et al, 2004). In a recent study of hormone levels in premenopausal women, there was a suggestive inverse association of birth weight with DHEAS (Tworoger et al, 2006), with which our adolescent DHEAS findings accord. Furthermore, it strengthens the evidence that it is valid for all birth size, and not only for SGA children.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…An inverse relation of birth size with adrenal androgen levels in 8-year-old children has also been found for children of normal birth size (Ong et al, 2004). In a recent study of hormone levels in premenopausal women, there was a suggestive inverse association of birth weight with DHEAS (Tworoger et al, 2006), with which our adolescent DHEAS findings accord. Furthermore, it strengthens the evidence that it is valid for all birth size, and not only for SGA children.…”
Section: Discussionsupporting
confidence: 80%
“…We observed a weak tendency for a positive association between birth size and adolescent oestradiol level. In two previous studies, both of which controlled for cyclic variation, positive associations of premenopausal oestradiol levels with ponderal index at birth (Jasienska et al, 2006) and birth weight (Tworoger et al, 2006) were reported. If this relation is true, it may be in accord with the positive association of birth size with BC risk observed in many studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, epidemiologic data seem to indicate that the association of high birth weight with breast cancer risk in premenopausal women is not likely to be mediated through height, weight, or growth velocity in childhood and adolescence (159,160), but possibly through greater adult height (161). Whether birth size is associated with premenopausal estrogen concentrations (162,163) or adult IGF profiles (164-167) is unclear.…”
Section: Prenatal Risk Factors For Breast Cancer Cancer Epidemiol Biomentioning
confidence: 99%
“…15 GWG and prepregnancy BMI are inversely associated with sex hormone binding globulin levels during pregnancy, which in turn increases levels of bioavailable estrogen. 16,17 A highly estrogenic environment in utero has been suggested to increase the risk of breast cancer, 18 which may be partly mediated by mammographic density. 19 However, GWG is also positively associated with birth weight, 20 which may be positively associated with mammographic density at least in postmenopausal women, although data are limited.…”
Section: Discussionmentioning
confidence: 99%